Shear strength of palm oil clinker concrete beams - Mohammed B.S.; Foo W.L.; Hossain K.M.A.; Abdullahi M. (2023)
This paper presents experimental results on the shear behavior of reinforced concrete beams made of palm oil clinker concrete (POCC). Palm oil clinker (POC) is a by-product of palm oil industry and its utilization in concrete production not only solves the problem of disposing this solid waste but also helps to conserve natural resources. Seven reinforced POCC beams without shear reinforcement were fabricated and their shear behavior was tested. POCC has been classified as a lightweight structural concrete with air dry density less than 1850kg/m3 and a 28-day compressive strength more than 20MPa. The experimental variables which have been considered in this study were the POCC compressive strength, shear span-depth ratio (a/d) and the ratio of tensile reinforcement (?). The results show that the failure mode of the reinforced POCC beam is similar to that of conventional reinforced concrete beam. In addition, the shear equation of the Canadian Standard Association (CSA) can be used in designing reinforced POCC beam with ??1. However, a 0.5 safety factor should be included in the formula for ?<1. 2012 Elsevier Ltd.